Accurate calling of KIAA1549‐BRAF fusions from DNA of human brain tumours using methylation array‐based copy number and gene panel sequencing data. (17th January 2021) - Stichel, Damian; Schrimpf, Daniel; Sievers, Philipp; Reinhardt, Annekathrin; Suwala, Abigail K.; Sill, Martin; Reuss, David E.; Korshunov, Andrey; Casalini, Belén M.; Sommerkamp, Alexander C.; Ecker, Jonas; Selt, Florian; et al.
Abstract: Aims: KIAA1549 ‐ BRAF fusions occur in certain brain tumours and provide druggable targets due to a constitutive activation of the MAP‐kinase pathway. We introduce workflows for calling the KIAA1549 ‐ BRAF fusion from DNA methylation array‐derived copy number as well as DNA panel sequencing data. Methods: Copy number profiles were analysed by automated screening and visual verification of a tandem duplication on chromosome 7q34, indicative of the KIAA1549 ‐ BRAF fusion. Pilocytic astrocytomas of the ICGC cohort with known fusion status were used for validation. KIAA1549 ‐ BRAF fusions were called from DNA panel sequencing data using the fusion callers Manta, Arriba with modified filtering criteria and deFuse. We screened DNA methylation and panel sequencing data of 7790 specimens from brain tumour and sarcoma entities. Results: We identified the fusion in 337 brain tumours with both DNA methylation and panel sequencing data. Among these, we detected the fusion from copy number data in 84% and from DNA panel sequencing data in more than 90% using Arriba with modified filters. While in 74% the KIAA1549 ‐ BRAF fusion was detected from both methylation array‐derived copy number and panel sequencing data, in 9% it was detected from copy number data only and in 16% from panel data only. The fusion was almost exclusively found in pilocytic astrocytomas, diffuse leptomeningeal glioneuronal tumours and high‐grade astrocytomas with piloid features. Conclusions: The KIAA1549 ‐ BRAF fusion can be reliably detected from either DNA methylation array or DNA panel data. The use of both methods is recommended for the most sensitive detection of this diagnostically and therapeutically important marker. Abstract : KIAA1549‐BRAF fusions occur in certain brain tumours and provide druggable targets due to a constitutive activation of the MAP‐kinase pathway. We show that the KIAA1549‐BRAF fusion can reliably be called from DNA methylation array‐derived copy number data as well as DNA panel sequencing data.